Lady in the lake : a novel - Lippman, Laura, 1959- (William Morrow, an imprint of HarperCollinsPublishers, 2019)
"New York Times bestseller Laura Lippman returns with a new stand-alone novel about a middle aged housewife turned aspiring reporter Maddie Schwartz, who is determined to solve the murder of a forgotten young woman in order to make her own reputation"--